Água: qualidade, interações ambientais e implicações socioeconômicas no estudo de caso do Lago dos Tigres (GO) - Oliveira, Juliano Eduardo de (2012)
The process of expansion and occupation of Goiás was based on farming practices. The municipality of Britain emerges in this context of agrarian expansion, in which the land is located where the city were bought and sold as small rural. The city has much of its economy facing livestock, however other activity has been increasing in the region such as tourism, which attracts hundreds of people there due to the Lago dos Tigres. The lake is the main postcard of the region, possessing 24km long and being located in the basins of the rivers Araguaia-Tocantins, this lake is formed by the meeting of the waters of the Rivers and Clean Water Red and that, combined with the local geography form a valley blocked. The lake has over time shown signs of environmental degradation due to the way the two main economic activities of the municipality using its resources. For this reason, the objectives of this study were: to survey, the main socioeconomic characteristics of the city, establishing the main income-generating activities in the region and see how these activities can impact upon quality of life of the local population and water quality lake. Also we made a characterization of the spatial evolution of the use and occupation of land in the county between the years 1988.1998 and 2009, in order to check how busy it was and how soil surrounding the Lake of the Tigers, was also verified how of land in the watershed may be interfering with the dynamics and interaction of phytoplankton communities and ficoperifíticas littorallimnetic gradient in the lake, as well as to analyze the influence of the hydrological cycle on these communities. The socioeconomic characteristics of the municipality of Britain was made with secondary data concerning agriculture, livestock, tourism, demographics, social and cultural region in the last ten years. Specific data on the region's economic development and the importance of the lake to the population were made through questionnaires. An Index of Sustainable Development for Municipalities (IDSM) was used to assess levels of sustainability in the region. The results highlighted the importance of the lake for the Tigers has the city's economy and for local people and how these activities are interfering with the water quality of the lake and in the diversity of species of algae that are the base of the food chain in aquatic system. The study found that deforestation in the region is endangering the Lake of the Tigers, and that this presents a direct relationship between man and water, harming the quality of life of people living in Britain. The reflection of local environmental change is reflected in the trophic status of the oligotrophic lake that already features indicative of transition to mesotrofia. The communities ficológicas not yet had major changes in its structure with significance. However, in recent years with morphological changes of the lake changes occurred in some aspects limnóligicos and this occurred with the rise of cyanobacteria at the site, indicating possible disturbances that may affect the water quality of the lake.